Transanal total mesorectal excision for rectal cancer: the journey towards a new technique and its current status. Issue 11 (1st November 2016) - Penna, Marta; Buchs, Nicolas C.; Bloemendaal, Alexander L.; Hompes, Roel
ABSTRACT: Introduction: The surgical approach to total mesorectal excision (TME) for rectal cancer has undergone a substantial evolution with the adoption of more minimally invasive procedures. Transanal TME (taTME) is the latest advanced technique pioneered to tackle difficult pelvic dissections. Areas covered: The evolution of TME surgery from open to laparoscopic, robotic and transanal techniques was explored in this review. The outcomes to date on the latest approach, taTME, are reviewed and the future direction of rectal cancer surgery proposed. A literature search was performed using Embase, Medline, Web of Science and Cochrane databases for articles published between January 2005 to May 2016 using the keywords 'transanal', 'TME', 'laparoscopy', 'robotics', 'minimally invasive', 'outcomes' and 'training'. Expert c ommentary: Surgical experience in taTME is growing and randomised controlled trials have been planned and initiated worldwide. However, the learning curve for this procedure remains to be established and a structured training programme is necessary to ensure safe introduction and dissemination of the technique in the clinical setting. Further innovation including stereotactic navigation and more specialised transanal equipment are currently being explored and are likely to enhance the technique further.